A new chalcone from the aerial roots of Ficus microcarpa - Xu, Hui; Wang, Xiang Min; Wei, Xing; Li, Jing Yuan; Liu, Ke (Chinese chemical letters, 2009)
A new flavonoid with chalcone skeleton was isolated from the dried aerial roots of Ficus microcarpa. The structure of the compound was elucidated on the basis of spectral methods including 1D and 2D NMR. The new compound showed weak inhibitory effect on nitric oxide production and cytotoxicity against K562 and PC3 cells.